2020
DOI: 10.3390/agronomy10070948
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Traits and Phenolic Compounds in Tunisian Wild Populations and Cultivated Varieties of Portulaca oleracea L.

Abstract: This study aims to evaluate the bio-morphological and biochemical variability of three Tunisian wild populations and one growing cultivar of purslane (Portulaca oleracea L.). The studied varieties should be easily distinguished by the color and the habitus of the plant as mentioned in literature, but the various analyses have shown a strong morphological heterogeneity within and among the wild and cultivated accessions as presented by the variance analysis test (ANOVA) and the PCA (Principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
6
3
1
Order By: Relevance
“…Independently from the solvent used for extraction, flavonoid contents were significantly higher in leaves than stems. These results are in accordance with those of Xu et al [6], who reported kaempferol and apigenin compounds as the most abundant flavonoids, and also with findings of Sdouga et al [46], who reported myricetin and rutin as the major compounds in leaves and stems, respectively. By contrast, Zhu et al [7] found that total flavonoid contents were higher in stems than leaves.…”
Section: Flavonoids Contentsupporting
confidence: 93%
See 4 more Smart Citations
“…Independently from the solvent used for extraction, flavonoid contents were significantly higher in leaves than stems. These results are in accordance with those of Xu et al [6], who reported kaempferol and apigenin compounds as the most abundant flavonoids, and also with findings of Sdouga et al [46], who reported myricetin and rutin as the major compounds in leaves and stems, respectively. By contrast, Zhu et al [7] found that total flavonoid contents were higher in stems than leaves.…”
Section: Flavonoids Contentsupporting
confidence: 93%
“…Comparing the different extracts in both leaves and stems, a significantly higher content (p < 0.05) of total phenols was obtained in leaves in both ethanolic (13.92 mg g −1 ) and aqueous extracts (2.45 mg g −1 ). Furthermore, total phenol contents found in this study were higher than those found by Santiago-Saenz et al [75] and Sdouga et al [46]. Previously, Sicari et al [15] measured total phenol contents in dried leaves of P. oleracea in both aqueous methanolic extracts and ethanolic ones, and they found the highest contents in the latter.…”
Section: Total Phenols and O-diphenolscontrasting
confidence: 68%
See 3 more Smart Citations